Widely Tuneable Composition and Crystallinity of Graded Na1+xTaO3±δ Thin Films Fabricated by Chemical Beam Vapor Deposition - Corrado Garlisi; Petru Lunca Popa; Kevin Menguelti; Vincent Rogé; Marc Michel; Christèle Vergne; Jérôme Guillot; Estelle Wagner; William Maudez; Giacomo Benvenuti; Bianca Rita Pistillo; Emanuele Barborini (Nanomaterials, 2022)
Combinatorial approach has been widely recognized as a powerful strategy to develop new-higher performance materials and shed the light on the stoichiometry-dependent properties of known systems. Herein, we take advantage of the unique features of chemical beam vapor deposition to fabricate compositionally graded Na1+xTaO3±δ thin films with −0.6 < x < 0.5. Such a varied composition was enabled by the ability of the employed technique to deliver and combine an extensive range of precursors flows over the same deposition area. The film growth occurred in a complex process, where precursor absolute flows, flow ratios, and substrate temperature played a role. The deviation of the measured Na/Ta ratios from those predicted by flow simulations suggests that a chemical-reaction limited regime underlies the growth mechanism and highlights the importance of the Ta precursor in assisting the decomposition of the Na one. The crystallinity was observed to be strongly dependent on its stoichiometry. High under-stoichiometries (e.g., Na0.5TaO3−δ) compared to NaTaO3 were detrimental for the formation of a perovskite framework, owing to the excessive amount of sodium vacancies and oxygen vacancies. Conversely, a well-crystallized orthorhombic perovskite structure peculiar of NaTaO3 was observed from mildly under-stoichiometric (e.g., Na0.9TaO3−δ) to highly over-stoichiometric (e.g., Na1.5TaO3+δ) compositions.